Will Penang based companies perform better than the market? - Lean H.H.; Ting I.W.K. (Economics Bulletin, 2023)
This paper examines the antecedents of company's performance and compares the performance between Penang based companies and Non-Penang based companies from firm characteristics point of view for the period of 2004 to 2013. A static panel data structure is employed to examine firm characteristics' effect to firm performance. We find that the Penang based companies outperform Non-Penang based companies. Second, the previous year's performance has a positive impact to the current year's performance for Penang based companies but has a negative impact to the Non-Penang companies. Third, larger firm performs better for Malaysian public listed companies. Fourth, the Penang based companies with their larger investment in intangible assets perform better. Fifth, Malaysian public listed companies should maintain lower gearing in order to increase firm performance. Sixth, the Penang based companies with a higher growth rate and operating cash flow ratio would help in ensuring the firms perform better. Our findings could serve as an indicator in assessing firm characteristics on firm performance for Penang based public listed companies.